Implementation of Ban on Serology Tests and Mandatory TB Notification - Dr. Arathi VA (Journal of Clinical and Biomedical Sciences)
Tuberculosis (TB) is the leading infectious cause of death worldwide. In 2014, the inci-dence of TB was estimated to be 9.6 million, (5.4 million men, 3.2 million women and 1.0 million children). TB killed 1.5 million people worldwide.[1] India is the highest TB burden country in the world, having an incidence of 1.98 million cases annually. Mortality is dispro-portionately high, of 1000 deaths/day, ac-counting to 280,000 each year. India also leads the world by having maximum number of Multi drug resistance cases (MDR) with an estimated 61,000 among all pulmonary TB cases. India has an estimated 2.2 % MDR among new TB cases and 15% among the previously treated TB cases.[2] Government of India (GoI) declared TB as a notifiable disease in 2012 making it mandatory for all private health establish-ments including clinical laboratories, allopathic hospitals, clinics, nursing homes and individual allopathic private practitioners (PPs) to regis-ter with the revised national TB control pro-gramme (RNTCP) for notifying the cases diag-nosed and /or treated by them to the govern-ment authorities.[3]